Construction of sluice gate building / Muhammad Amir Danial Ismail - Ismail, Muhammad Amir Danial (Universiti Teknologi MARA, Perak, 2022)
The sluice gate building is a very important structural element for controlling the irrigation of water between seawater and land water. Then, sluice gates also play a role are used to regulate the flow of water in canals. To obtain a goal flow rate for a specified time period, gates are manually raised or lowered and then left in place. This report was discussed about and conducted for the construction of sluice gate building at 170, Jalan 7 in Bagan Sungai Besar, 45300 Mukim Sungai Besar, Daerah Sabak Bernam, Negeri Selangor. The objective of this report is to explain the method of construction temporary road. This report will focus on the installation process of sheet pile. It also to describe the types of sheet pile used and identify the problem faced during construction. So, building sluice gates is important to control water irrigation to prevent flooding occurs when the water level in the canal rises too high, affecting the community. Flooding may also ruin irrigated plants, paddy, and vegetable cultivations, among other things.